2006
DOI: 10.1002/mnfr.200500187
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of isoflavone aglycones from soy and red clover

Abstract: Driven by their beneficial effects on human metabolism, isoflavonoids have gained considerable importance reflected by an increased number of isoflavone-rich foods, food supplements and pharmaceutical products on the market, mainly derived from soy and red clover. While it is well known that the genuine isoflavone pattern will be altered during processing, data on aglycone stability are rare. Therefore, a thorough study into the thermal sensitivities of biochanin A, daidzein, formononetin, flavone, genistein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
5
23
0
1
Order By: Relevance
“…However, aglycones content in soybean dried at 150°C was lower than that in soybean dried at 130°C. Recent data revealed that aglycones exhibit higher degradation rates when heated at 150°C or higher (Chien et al, 2005;Stintzing, Hoffmann, & Carle, 2006;Xu et al, 2002). It is possible that the inter-conversion from several glucosides to the corresponding aglycones via hydrolysis occurred at lower extents compared to the thermal degradation of aglycones at the drying temperature of 150°C.…”
Section: Effect Of Drying On Distribution Of Isoflavones In Soybeanmentioning
confidence: 94%
“…However, aglycones content in soybean dried at 150°C was lower than that in soybean dried at 130°C. Recent data revealed that aglycones exhibit higher degradation rates when heated at 150°C or higher (Chien et al, 2005;Stintzing, Hoffmann, & Carle, 2006;Xu et al, 2002). It is possible that the inter-conversion from several glucosides to the corresponding aglycones via hydrolysis occurred at lower extents compared to the thermal degradation of aglycones at the drying temperature of 150°C.…”
Section: Effect Of Drying On Distribution Of Isoflavones In Soybeanmentioning
confidence: 94%
“…Besides, considering the reports that isoflavones are sensitive to oxidation, particularly under basic conditions at elevated temperatures [41][42][43], the appropriate control experiments to study the template decomposition during synthesis process were performed. It concerned, the comparison of the chromatograms obtained from the analysis of the standard of biochanin A and methanol extracts of Soxhlet extraction, used for template removal.…”
Section: The Preparation Of the Bca-surface Imprinted Silica Particlesmentioning
confidence: 99%
“…The stability of biochanin and formononetin at 90°C for 5 min has previously been demonstrated (Stintzing et al, 2006). The freeze-dried leaf samples (50 ± 2.5 mg samples) were extracted x1 in 0.…”
Section: Methodsmentioning
confidence: 81%